Flora and vegetation associated with the stands of Puya raimondii from Huarochiri, Lima, Peru - Aquino Torres, Willy Elias (2019)
Puya raimondii Harms is endemic of Peru and Bolivia Andes, their populations are distributed between 3500 and 4800 m of altitude; living on rocky soils with moderate to very strong slopes. In this paper, we present a inventory of the flora and vegetation associated Puya raimondii stands. Intensive botanical collections were carried out in Huarochirí, during wet and dry seasons of 2016 and 2017 years. A total of 172 species grouped in 114 genera and 51 families were registered. The families most diverse were Asteraceae (44 species), Poaceae (23), Brassicaceae (8) and Fabaceae (8). Growth habits dominant were herbs (81.4%) and bushes (17.4%). Cerro Piño-Huaquinanchi stand had 74% of the total flora, Huajlasana 67.5% and the Pacchapuquio stand 61%. There were 16 endemic species of Peru; additionally, nine species were categorized by Peruvian legislation and three by IUCN. Finally, 45 new records were registered for Lima region, evidencing the lack of botanical inventories in the high Andean regions and the need to continue carrying out studies in high mountain ecosystems.